A Tool for Improving Mediations: Informed Pairings and Predictive Outcomes - Shaphan Roberts (Washington University Journal of Law & Policy, 2019)
This paper examines the Community Police Unification Program (“CPU”), a collaboration between the Los Angeles Police Department (“LAPD”) and the Los Angeles City Attorney’s office that offers a tool for effectively pairing mediators to cases. First, this paper briefly explores the need for such a mediation program to facilitate communication between LAPD and the community it serves. The paper then explores the uniqueness of CPU cases and the need for correctly pairing mediators. Finally, the paper discusses the strengths, weaknesses and areas for improvement when developing a pairing tool for such a program.
Keywords: Community Police Unification Program; Los Angeles Police Department; LAPD; Los Angeles City Attorney; mediators; mediation